2007
DOI: 10.1038/sj.eye.6702736
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of cataract surgery in a cohort of Tanzanians with operable cataract

Abstract: Background In spite of recent increases in the number of surgeries carried out within some hospitals and programmes in sub-Saharan Africa, there are indications that the acceptance of cataract surgery remains quite low. Methods We conducted a population-based prospective (cohort) study of cataract patients from 12 villages in Hai district of Kilimanjaro region, Tanzania. Those identified with operable cataract were informed of the regular community programmes (within 5 km) in place providing transportation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 9 publications
(10 reference statements)
2
10
1
Order By: Relevance
“…In this study, about thirty-nine percent of corneal transplantation indicated patients had accepted the transplantation. is result is higher than the study finding of cataract surgery in Tanzania (17.8%) [11]. e possible justification for this discrepancy could be the difference in the study design; the current study was cross-sectional, while the study in Tanzania was cohort.…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, about thirty-nine percent of corneal transplantation indicated patients had accepted the transplantation. is result is higher than the study finding of cataract surgery in Tanzania (17.8%) [11]. e possible justification for this discrepancy could be the difference in the study design; the current study was cross-sectional, while the study in Tanzania was cohort.…”
Section: Discussioncontrasting
confidence: 61%
“…Our findings indicate that by recruiting patients with cataract who are younger and/or have better pre-operative VA, a reduction in the proportion of poor outcomes may be possible. A cohort study of patients with operable cataract from Tanzania in close proximity to an eye care programme found that only 23 % of potential cataract surgical candidates had blindness or severe visual impairment, and that the elderly were the least likely group to accept free surgery [24]. This suggests that other measures in addition to visual acuity, such as vision-related quality of life, may be useful to select patients for surgery, and may reduce the likelihood of a poor outcome.…”
Section: Discussionmentioning
confidence: 93%
“…We believe that there are more elderly blind who do not attend and they might not be represented by the population we studied. However, other population-based data from the same area also indicate that cataract acceptance rates are low even when surgery is free and transport is provided 11. One might argue that the true test of how cost affects acceptance would be a randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%